Perceived Burdens and Benefits Associated With Continuous Glucose Monitor Use in Type 1 Diabetes Across the Lifespan. (January 2022) - Divan, Vidita; Greenfield, Margaret; Morley, Christopher P.; Weinstock, Ruth S.
Background: Continuous glucose monitors (CGMs) help people with type 1 diabetes (T1D) improve their glycemic profiles but are underutilized. To better understand why, perceived CGM burdens and benefits in nonusers versus users with type 1 diabetes across the lifespan were assessed. Methods: Burdens (BurCGM) and benefits of CGM (BenCGM) questionnaires were completed during T1D outpatient visits ( n = 1334) from February 2019 to February 2020. Mean scores were calculated (scale one to five; higher scores reflect greater perceived burdens/benefits). Data were collected from medical records including glycated hemoglobin (HbA1c) within 3 months of the visit. Results: Individuals of all ages using CGM described more benefits and less burdens (mean scores 4.48 and 1.69, respectively) when compared with those who were not using CGM (mean score 4.19 and 2.35, respectively) ( P < .001). There were no differences in burdens or benefits by sex. Non-CGM users aged ≥50 years had higher mean BurCGM scores than those aged <50 years ( P = .004); the cost was the greatest barrier in those aged 27+ years. Other burdens were readings not trusted, painful to wear, and takes too much time to use. For those aged 65+, nonusers versus users, 18.5% versus 3.1% agreed with "it was too hard to understand CGM information, " and 21.4% versus 7.7% agreed that CGM causes too much worry. Mean HbA1C was lower in CGM users (8.1%) versus non-CGM users (mean A1c 9.1%; P < .001). Conclusions: CGM was perceived as having more burdens and less benefits in nonusers, with differences in concerns varying across the lifespan. Lower costs and age-appropriate education are needed to address these barriers.